Tropical and Extratropical Wave Disturbances Impact on the Amazon Basin Precipitation: Subseasonal to Intraseasonal Timescales - Chávez Mayta, Víctor Raúl (2019)
Descargue el texto completo en el repositorio institucional de la Universidade de São Paulo: https://doi.org/10.11606/T.14.2019.tde-06082019-134442